The earliest case of extreme sexual display with exaggerated male organs by two Middle Jurassic mecopterans. - Qi Wang (Public Library of Science (PLoS), 2013)
Background Many extant male animals exhibit exaggerated body parts for display, defense or offence in sexual selection, such as male birds of paradise showing off colorful and elegant feathers and male moose and reindeers bearing large structured antlers. For insects, male rhinoceros and stag beetles have huge horn-like structure for fighting and competition and some male Leptopanorpa scorpionflies have very long abdominal terminal segments for sexual display and competition. Fossil records of insects having exaggerated body parts for sexual display are fairly rare. One example is two male holcorpids with elongate abdominal segments from sixth (A6) to eighth (A8) and enlarged male genitalia from Eocene, suggesting evolution of these characters occurred fairly late. Principal findings We document two mecopterans with exaggerated male body parts from the late Middle Jurassic Jiulongshan Formation in northeastern China. Both have extremely extended abdominal segments from A6 to A8 and enlarged genitalia, which might have been used for sexual display and, to less extent, for fighting with other males in the competition for mates. Although Fortiholcorpa paradoxa gen. et sp. nov. and Miriholcorpa forcipata gen. et sp. nov. seem to have affinities with Holcorpidae, we deem both as Family Incertae sedis mainly due to significant differences in branching pattern of Media (M) veins and relative length of A8 for F. paradoxa, and indiscernible preservation of 5-branched M veins in hind wing for M. forcipata. Conclusions/significance These two new taxa have extended the records of exaggerated male body parts of mecopterans for sexual display and/or selection from the Early Eocene to the late Middle Jurassic. The similar character present in some Leptopanorpa of Panorpidae suggests that the sexual display and/or sexual selection due to extremely elongated male abdominal and sexual organs outweigh the negative impact of bulky body and poor mobility in the evolutionary process.